Human resource development and job satisfaction among nurses - Suprapto, Suprapto; Lalla, Nursyamsi Norma; Mulat, Trimaya Cahya; Arda, Darmi (Intelektual Pustaka Media Utama, 2023)
The skills of a good nurse manager, the quality and quantity of human resources, and the development of human resources to face changes both the internal and external environments begin with building nurses' commitment to various indicators of human resources development in hospitals that have an impact on customer or patient satisfaction. Quantitative research with an analytical observational approach was conducted in hospitals, with a sample of 136 nurses from the population obtained by probability sampling. The results of the statistical test that training is the human resources development factor that most affect the job satisfaction of nurses in hospitals with an Exp (B) ratio or odds of 1.790, indicating that nurses with more specialized training tend to be 1.790 times more satisfied than nurses with less specialized training, and that this is also true since their Exp B grades are good. This study concludes that training has a big impact on how happy nurses are. As healthcare providers in hospitals, nurses need to optimize their abilities and competencies to raise the standard of nursing care. Nursing directors are essential in building and recruiting, and measuring nurse competencies.